RELEVANSI NILAI-NILAI PENDIDIKAN KARAKTER DALAM KITAB TA’LIM MUTA’ALLIM TERHADAP MATERI PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Ummi Lailia Maghfiroh; Ali Zainal Abidin (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
Character education is carried out in an integrated manner to form the personality traits of students as a whole which is reflected in behavior in the form of words, actions, attitudes, thoughts, feelings, work, and good work. education. The book Ta'limul Muta'allim is a book written by Syekh al-Zarnuji which contains ethics that must be upheld by students. So that in the discussion of this book, it is very relevant to the character education that students must have. The value of character education in the Book of Ta'limul Muta'allim has a relevance that deserves to be considered for actualization and implementation in Islamic Religious Education. This research is designed using library research, which is research based on analysis of sources in the form of library books, papers, articles, journals and other relevant library materials. Based on the results of the research using the procedures described in the previous chapters, the following conclusions can be drawn: (1) The values ​​of character education in the book Ta'lim Muta'allim by Syekh al-Zarnuji that have been found by the author are 16 character values , namely: love of knowledge, love of peace, democratic, friendly / communicative, tawadlu ', sincere, diligent, tawakal, patient, and honest (2) The relevance of character education values ​​in the Ta'lim Muta'allim book to education material Islam and Character at the SMPI level are: love of knowledge, love of peace, tawadlu ', smart, tawakal, patient. Keywords: Educational Values, Book of Ta'lim Muta'allim, Islamic Religious Education